Mechanosensing is critical for axon growth in the developing brain - Koser, David E.; Thompson, Amelia J.; Foster, Sarah K.; Dwivedy, Asha; Pillai, Eva K.; Sheridan, Graham K.; Svoboda, Hanno; Viana, Matheus; Costa, Luciano Da F.; Guck, Jochen; Holt, Christine E.; Franze, Kristian (Nature Neuroscience, 2016)
During nervous system development, neurons extend axons along well-defined pathways. The current understanding of axon pathfinding is based mainly on chemical signaling. However, growing neurons interact not only chemically but also mechanically with their environment. Here we identify mechanical signals as important regulators of axon pathfinding. In vitro, substrate stiffness determined growth patterns of Xenopus retinal ganglion cell axons. In vivo atomic force microscopy revealed a noticeable pattern of stiffness gradients in the embryonic brain. Retinal ganglion cell axons grew toward softer tissue, which was reproduced in vitro in the absence of chemical gradients. To test the importance of mechanical signals for axon growth in vivo, we altered brain stiffness, blocked mechanotransduction pharmacologically and knocked down the mechanosensitive ion channel piezo1. All treatments resulted in aberrant axonal growth and pathfinding errors, suggesting that local tissue stiffness, read out by mechanosensitive ion channels, is critically involved in instructing neuronal growth in vivo.
CRIS-Team Scopus Importer:2020-08-12